Is the declaration of Alma Ata still relevant to primary health care?. Issue 7643 (6th March 2008) - Gillam, Stephen
Abstract : Thirty years after WHO highlighted the importance of primary health carein tackling health inequality in every country, Stephen Gillam reflects on the reasons for slow progress and the implications for today's health systems